The Role of Magnetic Resonance Imaging of the Temporomandibular Joint to Investigate Tinnitus in Adults with Temporomandibular Joint Disorder: A Comparative Study - Lavinsky,Danielle (2020)
Abstract Introduction The prevalence of tinnitus is higher in individuals with temporoman- dibular joint disorder (TMD) than in the general population. Magnetic resonance imaging (MRI) of the temporomandibular joint (TMJ) is the method of choice for investigation, and it has been hypothesized that speciﬁc MRI ﬁndings might be observed in TMD with comorbid tinnitus. Objective To comparatively describe MRI ﬁndings in patients with TMD with and without tinnitus, identifying the most common TMJ alterations and determining whether a correlation exists between severity of TMD and tinnitus. Methods A cross-sectional study of 53 adult patients with bilateral or unilateral TMD (30 with and 23 without tinnitus). The association between tinnitus and morphological aspects of TMD (changes in condylar morphology, articular eminence morphology, and disc morphology), disc displacement (with/without reduction), condylar translation, and intra-articular effusion was analyzed on MRI images. Results The mean patient age was 46.12 ± 16.1 years. Disc displacement was the most common ﬁnding in both groups (24 patients with tinnitus versus 15 without; p = 0.043). Only the frequency of disc displacement with reduction was signiﬁcantly different between groups. Conclusion Additional imaging techniques should be explored to detect speciﬁc aspects of the relationship between tinnitus and TMD.